Assessing Sources of Information for Urban Mushroom Growers in Accra, Ghana. Issue 2 (3rd April 2018) - Kavi, Raphael Kwame; Bugyei, Kwabena Asiedu; Obeng-Koranteng, Grace; Folitse, Benjamin Yao
ABSTRACT: This study assessed information sources for urban mushroom farmers in Accra, Ghana. One hundred farmers were sampled, and a structured questionnaire was administered to solicit information from the respondents. Results showed that the majority of farmers were male (71%) and most (60%) with university education. The majority (44%) had 1–5 years of experience in mushroom cultivation. Co-farmers (89.8%), the Mushroom Growers Association (79.6%), training workshops (73.5%), and the Farmers' Forum (29.6%) readily served as information sources for farmers. The research revealed that, for 52% of farmers, ignorance of information sources was a major hindrance in their quest for information.